ETIOLOGICAL AND PATHOLOGICAL STUDY OF EPIDEDE/lY'I‘IS IN GOATS IN BAGHDAD CITY - Al-Obaidil , Amir S.R.; Alwan, Mohammed J.; Al-Khaisi , Bushrah ‘ I. (The Iraqi Journal of Veterinary Medicine, 2022)
Testes from 700 male goats aged l - 3 years , slaughtered at Baghdad abatteir, were examined during 6 months period. Histological and bacteriological examinations were done when gross lesions were observed. The results revealed that epidedimytis was observed in 21 (3%) of the examined animals ; 16 (2.3%) cases were unilaterally affected and S (0.7%) cases were bilaterally affected.Bacteriological isolations from infected organs included :Corynebacterium ovis (6 isolates) and Actinomyces pyogenes (3 isolates) both constituted the majonty of isolates ; as well as E. coli (4 iso-lates), and Pseudomonas aeruginosa , Staphylococcus epidermidis, Cory. bovis., Staph. aureus, Cory , ulcerams &. Yersinia pseuclotuberculosis ( 2 isolates of each ) and Campylobacter fetus (1 isolate).Histopathological examination showed 6 pathological patterns of epididmytis including acute epididymitis (14.2% of infected cases ) , subacute nomsuppurative epididymilis (9.5% od cases ) , chronic suppurative epididymitisd (28.5% of cases ), chronic non—suppurative epididymitis (19% of cases) and spermatic granuloma (14.2% of cases ).